Construction Efficiency in Shear Strengthening of Pre-Cracked Reinforced Concrete Beams Using Steel Mesh Reinforced Strain Hardening Cementitious Composites - Sabry Fayed; Mohamed Ghalla; Ayman El-Zohairy; Ehab A. Mlybari; Rabeea W. Bazuhair; Mohamed Emara (Buildings)
Because of the degradation of building materials and the increased design load, concrete parts continually require repair. Special cementitious matrix components, Strain Hardening Cementitious Composites (SHCC), have exceptional ductility, strength growth during cracking, and recurrent controlled-opening crack formation. The purpose of this study was to improve the qualities of SHCC by reinforcing it with steel metal mesh. This study examined the optimization and effects of shear strengthening on the shear capacity of both damaged and undamaged reinforced concrete beams by employing SHCC internally reinforced with steel mesh fabric (SMF). Under bending loading, eight reinforced concrete beams were evaluated. Four of them were loaded to shear crack before any strengthening could be performed. The beams were 1500 mm in length, 200 mm in height, and 120 mm in width, and one, two, or three SMFs were applied. The beams’ whole shear span had external strengthening applied on both sides. Additionally, layers of strengthening in the U-shape were applied. The walls of the strengthening were thirty millimeters thick. The failure, load-deflection response, ultimate load, ultimate displacement, and energy absorbance of the tested beams were determined and discussed. Compared to an unstrengthened beam, the ultimate load of undamaged beams increased by 47%, 57%, and 90% when reinforced with 1, 2, or 3 layers of SMF, respectively, within the SHCC. Additionally, incorporating one, two, or three SMF layers within the SHCC improved the deflection of strengthened undamaged beams by 52%, 87%, and 116%, respectively. For damaged beams, the maximum load was approximately 11% lower than that of their undamaged counterparts, regardless of the number of SMF layers used in the SHCC strengthening. Applying one, two, or three layers of SMFs within the strengthening layer led to increases of the ratios of 163, 334, and 426%, respectively, in the energy absorbed by the strengthened beams in comparison to the control beam. The shear strength of the strengthened beams was determined through analytical modeling by implementing a correction factor (α = 0.5) to take into consideration the debonding action between the SHCC layer and the beam sides. This factor significantly improved the predictive accuracy of the analytical models by matching the mean ratio of the analytical findings to the experimental predictions.